PENDAFTARAN PRAKTIKUM PADA JURUSAN TEKNIK INFORMATIKA UNIVERITAS PALANGKA RAYA BERBASIS WEBSITE (Universitas Palangka Raya, 2017)
Department of Informatics at the University of Palangkaraya there are many courses offered. Of the many courses offered there are some subjects that requires students to follow the lab. Each student must semester must register lab if taking practical subjects. However, when applying practicum students must queue up to register the practicum and adjust the schedule with the schedule practicum course.In the task this practice created a web application information system named